Foreign Countries of Old Age - Gramshammer-Hohl, Dagmar; Ursulesku, Oana (transcript Verlag, 2020)
Long description: The exploration of what May Sarton calls the »foreign country of old age« usually does not go far beyond the familiar: the focus of Aging Studies has thus far clearly rested upon North America and Western Europe. This multi-disciplinary essay collection critically examines conditions and representations of old age and aging in Eastern and Southeastern Europe from various perspectives of the humanities and social sciences. By shedding light on these culturally specific contexts, the contributions widen our understanding of the aging process in all its diversity and demonstrate that a shift in perspectives might in fact challenge a number of taken-for-granted positions and presumptions of Aging Studies
PublicationDate: 20200701
Keywords: Culture; history; Society; Education; Cultural History; Biopolitics; literature; Eastern European History; Slavic Studies; Family; Literary Studies; Aging; Aging Studies; Intergenerational Relationships; Eastern Europe; Demography; Dementia; Mythology; Ageism; Southeastern Europe; Balkans; Soziale Rolle; Alter; Generationenvertrag; Literatur; Osteuropa; Südosteuropa; Konferenzschrift -- 04.2017 -- Graz